Analyzing the Influence of BRI Foreign Direct Investment on Governance: Perspective from Southeast Asian Countries. (May 2023) - Liu, Qian; Wang, Yingying; Kang, Ning
Promoting international economic cooperation plays a vital role in improving global governance. International cooperation benefits participating countries economically, and positively impacts their social development and national governance. Based on the micro survey data of eight Southeast Asian countries, this article analyzes the influence mechanism of the Belt and Road outward foreign direct investment (FDI) on the governance of the host countries. The article finds that China's outward FDI, through its positive role in the host country's economic and social development, leads to a positive perception among people in host countries regarding China's influence locally. On the one hand, it enhances people's sense of identity with China's development. On the other hand, it contributes to people's satisfaction with their local government, thereby improving national governance. The findings of this article offer theoretical insights for promoting high-level opening-up. When participating in global governance, one must pay attention to the real sense of gain in the host countries and their people, improve the governance and promote high-quality development of regional economic cooperation.